مشكلات التعلم عن بعد دراسة مقارنه بين المدارس الأردنية والفلسطينية - محمد حداد, نيفين; علي سبتان كعبية, مثقال (Journal of College of Education, 2022)
The study aimed to identify the detection of distance learning problems, a comparative study between Jordanian and Palestinian schools in Jordan, through the application on a sample of (1000) male and female teachers within the Green Line and Irbid Governorate. A tool was developed for the study consisting of (20) paragraphs, and after verifying the validity of the tool. Its stability was applied to the electronic sample. The study reached the following results: The problems of learning about in Palestine and Jordan were moderate, where the evaluation problems came in the first place, while the problems related to teaching methods came in the last place, noting that the level of problems in Jordan was higher than in Palestine in all areas and the administration as a whole.The results showed that there were statistically significant differences in distance learning problems according to the gender variable, in favor of females in Palestine and in favor of males in Jordan, and no statistically significant differences were found due to the variables of years of experience or educational qualification in the two study areas. The researcher recommended a number of recommendations, the most important of which was the development of education platforms to allow the teacher to conduct different types of assessment and that the assessment is not limited to one type as is the case today, and to update school infrastructure so that those structures support synchronous distance learning applications through the ZOOM application ) or other applications that allow the teacher and student to synchronize while learning.
Keywords: problems; distance learning; COVID-19